Editorial: Cognitive Brain-Inspired Cyber-Physical Systems in Industrial Informatics - Sangaiah, Arun Kumar; Siarry, Patrick (Frontiers in Neurorobotics, 2022)
Furthermore, this research shows that the proposed protocol is effective in terms of the communication and computation cost in secure cloud storage of smart card–based healthcare information. The third paper by Li et al. has established a CNN algorithm model and applied it to the MRI image segmentation of patients with acute cerebral infarction to evaluate the effect of butylphthalide combined with edaravone treatment on the neurological function of patients. The success of the online experiment with five subjects demonstrates the simplicity and flexibility of the robotic arm control system in SSVEP-based BCI, which will be a practicable and promising application for disabled individuals in their daily lives.